2017
DOI: 10.1104/pp.17.01142
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of a Malate-Permeable Anion Channel, OsALMT4, Disrupts Mineral Nutrition

Abstract: ORCID IDs: 0000-0003-1555-4754 (J.L.); 0000-0003-3009-7854 (M.Z.); 0000-0002-1376-9543 (P.R.R.).Aluminum-activated malate transporters (ALMTs) form a family of anion channels in plants, but little is known about most of its members. This study examined the function of OsALMT4 from rice (Oryza sativa). We show that OsALMT4 is expressed in roots and shoots and that the OsALMT4 protein localizes to the plasma membrane. Transgenic rice lines overexpressing (OX) OsALMT4 released malate from the roots constitutively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 70 publications
(88 reference statements)
0
33
0
Order By: Relevance
“…Phylogenetic evolutionary analysis plays a vital role in realizing the function of gene families. In earlier studies, 14 ALMT genes in Arabidopsis were classified into three clusters [41]; 34 soybean ALMT genes that belonged to two main groups were further divided into six subgroups [44]; nine ALMT genes in rice were clustered into five clades [45]; 25 ALMT genes in Malus domestica were classified into seven subgroups [38]; 13 grape ALMT genes were clustered into three clades [46]. These results indicated a large phylogenetic evolutionary classification difference among various plant species.…”
Section: Discussionmentioning
confidence: 85%
“…Phylogenetic evolutionary analysis plays a vital role in realizing the function of gene families. In earlier studies, 14 ALMT genes in Arabidopsis were classified into three clusters [41]; 34 soybean ALMT genes that belonged to two main groups were further divided into six subgroups [44]; nine ALMT genes in rice were clustered into five clades [45]; 25 ALMT genes in Malus domestica were classified into seven subgroups [38]; 13 grape ALMT genes were clustered into three clades [46]. These results indicated a large phylogenetic evolutionary classification difference among various plant species.…”
Section: Discussionmentioning
confidence: 85%
“…GABA concentration oscillates over diel cycles and increases in response to multiple abiotic and biotic stresses including drought, heat, cold, anoxia, wounding pathogen infection and salinity 23 . ALMT have been implicated in modulating multiple developmental and physiological processes in plants 14, 15, 16, 34, 35, 36 including those underpinning nutrient uptake and fertilization that are affected by GABA 13, 37 . Therefore, our discovery that GABA regulates ALMT to form a novel and physiologically relevant signalling mechanism in guard cells is likely to have broad significance beyond stomata, particularly during plant responses to environmental transitions and stress.…”
Section: Discussionmentioning
confidence: 99%
“…Growth studies found that the OX lines were more sensitive to Mn toxicity but more tolerant of B toxicity than null plants. The authors conclude that enhancing OsALMT4 expression affected the compartmentation of malate within the tissues which increased Mn concentrations in the apoplast and caused the toxicity symptoms [39].…”
Section: Almt Members In Poaceaementioning
confidence: 99%
“…OsALMT4 is widely expressed in rice and encodes a malate-permeable anion channel on the plasma membrane. Enhancing OsALMT4 expression affected the compartmentation of malate within the tissues which increased Mn concentrations in the apoplast and caused the toxicity symptoms of dark brown spots and stripes and occasionally necrotic margins [39].…”
Section: Almt Genes Perform Various Functions Among Plantsmentioning
confidence: 99%
See 1 more Smart Citation